Invasive pathogen drives host population collapse: Effects of a travelling wave of sarcoptic mange on bare‐nosed wombats. Issue 1 (23rd August 2017) - Martin, Alynn M.; Burridge, Christopher P.; Ingram, Janeane; Fraser, Tamieka A.; Carver, Scott
Abstract: Emerging and invasive pathogens can have long‐lasting impacts on susceptible wildlife populations, including localized collapse and extirpation. Management of threatening disease is of widespread interest and requires knowledge of spatiotemporal patterns of pathogen spread. Theory suggests disease spread often occurs via two patterns: homogenous mixing and travelling waves. However, high‐resolution empirical data demonstrating localized (within population) disease spread patterns are rare. This study examined the spread of sarcoptic mange (aetiological agent Sarcoptes scabiei ) in a population of bare‐nosed wombats ( Vombatus ursinus ), and investigated whether pathogen spread occurred by homogenous mixing or a travelling wave. Using 7 years of population surveys and 4 years of disease severity surveys, we show that mange was first detected in the east of a wombat population in northern Tasmania, and progressed westward as a travelling wave. Wombat mortality rates reached 100% behind the wave, with a 94% decline in overall wombat abundance within the park. Synthesis and applications . Globally distributed pathogens may have severe impacts on susceptible host species. This is the first study to quantify population‐level impacts of sarcoptic mange upon bare‐nosed wombats, showing a wave of mange disease which resulted in a dramatic population decline. Successful management of the spread of this and similar pathogens may hinge on the capacity to establish transmission barriers at local or between‐population scales. Abstract : Globally distributed pathogens may have severe impacts on susceptible host species. This is the first study to quantify population‐level impacts of sarcoptic mange upon bare‐nosed wombats, showing a wave of mange disease which resulted in a dramatic population decline. Successful management of the spread of this and similar pathogens may hinge on the capacity to establish transmission barriers at local or between‐population scales.